As Operações com Terceiros no Direito Cooperativo Português: Comentário ao Acórdão do Supremo Tribunal de Justiça de 18 de Dezembro de 2007 - Meira, Deolinda Aparício (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2010)
Based on lhe analysis of a Supremo Court decision regarding the entitlement of the revenue resulting from purchases to third parties, we proceed to characterize the legal regime of such operations in the Portuguese Law, focusing on the concept of third party in cooperative societies and on the nature of the benefits arising from trading with externai parties. We conclude that. such benefits are construed as profits and not real surpluses from cooperative activity; therefore, in adherence to mutualist principies, benefits resulting from trading with third parties cannot be returned to the cooperative members and must be allocated to mandatory reserves.